Students and Scientists Connect with Nature in Uganda, East Africa - Johnson-Pynn, Julie S.; Johnson, Laura R.; Kityo, Robert; Lugumya, Douglas (International Journal of Environmental and Science Education, 2014)
We studied the impact of environmental education (EE) workshops on Ugandan youth’s (N = 84) perceptions of their relationship with nature, self efficacy, and civic attitudes and skills. Two nature-related measures and two measures related to social competencies were administered before and after EE workshops that were designed to educate youth about environmental conservation through field experiences with university scientists and inquiry-based activities with environmental educators. Pre- and post-workshop scores were analyzed using Mixed Design ANOVAs to determine if EE workshop program format length and setting differentially affected male (n = 43) and female (n = 41) participants’ perceived benefits of EE workshops. Participants’ scores increased following EE workshops, except those in the urban setting, who reported a decrease in their connections to nature compared to those in the rural setting. Longer workshops with more field experiences had the most profound impact on participants’ feelings of connection to nature, social competencies, and commitment to civic action. Males showed increases in self efficacy in the rural workshop and greater connectedness to nature in the longer workshops compared to females. Results underscore the importance of considering geographical and cultural contexts when developing and evaluating EE.
Keywords: Environmental education; Culture; Mentorship; Field experience; Africa